Development and Faith : Where Mind, Heart, and Soul Work Together - Marshall, Katherine; Van Saanen, Marisa (Washington, DC: World Bank, 2012)
This book aims to advance the shared understanding that is emerging from a dialogue on global development issues. It takes stock of a decade of exchanges and partnerships that have marked the effort to bridge what were too often diverging worlds. It recognizes the complexity and challenge inherent in dialogue on difficult issues, where conflicting views and areas of uncertainty abound. But it also highlights the wealth of experience gained. This is a book about partnerships between development and faith institutions. It is grounded in our common, abiding resolve to deepen our efforts to combat poverty, and it highlights several areas of shared focus and endeavor. The first section in this book focuses on the MDG framework and diverse faith-based and faith-secular partnerships that are tackling particular MDG dimensions. Chapter 2 discusses broad alliances among faith institutions inspired in good measure by the Millennium Development Goals (MDGs). This chapter highlights the engagement of these institutions in the global MDG mobilization, and their growing use of the MDG framework as a basis for advocacy and action. Chapter 3 turns to HIV/AIDS. Chapters 4 and 5 recount faith-based collaborations on other global health challenges, including malaria. These experiences underscore the challenges that remain in realizing the potential of faith development partnerships. Chapter 6 explores the complexities of one of the most vital challenges of the MDGs: bringing education to all. The final two chapters explore issues that are vital to the MDG framework but not highlighted as specific goals.